At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To find the zeros of the polynomial [tex]\( P(x) = x^3 - 2x^2 + 2x - 1 \)[/tex], we need to solve for [tex]\( x \)[/tex] such that [tex]\( P(x) = 0 \)[/tex].
Let's outline the steps involved:
1. Identify the Polynomial:
The polynomial given is [tex]\( P(x) = x^3 - 2x^2 + 2x - 1 \)[/tex].
2. Set the Polynomial Equal to Zero:
To find the roots, we need to solve:
[tex]\[ x^3 - 2x^2 + 2x - 1 = 0 \][/tex]
3. Find the Zeros:
By solving the equation [tex]\( x^3 - 2x^2 + 2x - 1 = 0 \)[/tex], we obtain the following roots:
[tex]\[ x = 1, \quad x = \frac{1}{2} - \frac{\sqrt{3}i}{2}, \quad x = \frac{1}{2} + \frac{\sqrt{3}i}{2} \][/tex]
Therefore, the zeros of the polynomial [tex]\( P(x) = x^3 - 2x^2 + 2x - 1 \)[/tex] are [tex]\( 1, \frac{1}{2} - \frac{\sqrt{3}i}{2}, \)[/tex] and [tex]\( \frac{1}{2} + \frac{\sqrt{3}i}{2} \)[/tex].
These roots include one real root, [tex]\( x = 1 \)[/tex], and two complex conjugate roots, [tex]\( x = \frac{1}{2} - \frac{\sqrt{3}i}{2} \)[/tex] and [tex]\( x = \frac{1}{2} + \frac{\sqrt{3}i}{2} \)[/tex].
Hence, the zeros of the polynomial [tex]\( P(x) = x^3 - 2x^2 + 2x - 1 \)[/tex] are: [tex]\( 1, \frac{1}{2} - \frac{\sqrt{3}i}{2}, \frac{1}{2} + \frac{\sqrt{3}i}{2} \)[/tex].
Let's outline the steps involved:
1. Identify the Polynomial:
The polynomial given is [tex]\( P(x) = x^3 - 2x^2 + 2x - 1 \)[/tex].
2. Set the Polynomial Equal to Zero:
To find the roots, we need to solve:
[tex]\[ x^3 - 2x^2 + 2x - 1 = 0 \][/tex]
3. Find the Zeros:
By solving the equation [tex]\( x^3 - 2x^2 + 2x - 1 = 0 \)[/tex], we obtain the following roots:
[tex]\[ x = 1, \quad x = \frac{1}{2} - \frac{\sqrt{3}i}{2}, \quad x = \frac{1}{2} + \frac{\sqrt{3}i}{2} \][/tex]
Therefore, the zeros of the polynomial [tex]\( P(x) = x^3 - 2x^2 + 2x - 1 \)[/tex] are [tex]\( 1, \frac{1}{2} - \frac{\sqrt{3}i}{2}, \)[/tex] and [tex]\( \frac{1}{2} + \frac{\sqrt{3}i}{2} \)[/tex].
These roots include one real root, [tex]\( x = 1 \)[/tex], and two complex conjugate roots, [tex]\( x = \frac{1}{2} - \frac{\sqrt{3}i}{2} \)[/tex] and [tex]\( x = \frac{1}{2} + \frac{\sqrt{3}i}{2} \)[/tex].
Hence, the zeros of the polynomial [tex]\( P(x) = x^3 - 2x^2 + 2x - 1 \)[/tex] are: [tex]\( 1, \frac{1}{2} - \frac{\sqrt{3}i}{2}, \frac{1}{2} + \frac{\sqrt{3}i}{2} \)[/tex].
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.